2014
DOI: 10.3109/01443615.2014.935720
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart disease and adverse perinatal outcome in fetuses with confirmed isolated single functioning umbilical artery

Abstract: To examine the association between isolated single umbilical artery (SUA) and congenital heart disease/adverse perinatal outcome in an Australian tertiary centre. The study population was comprised of fetuses diagnosed with SUA at the mid-trimester scan between May 2003 and March 2009 during detailed ultrasound examination at The Royal Women's Hospital Melbourne, Australia. Colour Doppler was used to visualise the umbilical arteries adjacent to the fetal bladder and in a section of a free loop of cord. The dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…This mechanism could explain our observation that in contrast to FOXF1 point mutations (Sen et al 2013b) and upstream deletion CNVs (Stankiewicz et al 2009; Szafranski et al 2013a; Szafranski et al 2014), genomic deletions of FOXF1 at its TAD boundary , and the flanking genes were associated with severe congenital heart defects, including hypoplastic left heart syndrome (HLHS) and SUA (Table 1 and Supplemental Table S1). Co-existence of HLHS and SUA has been well documented (Tasha et al 2014; Araujo et al 2015). We have previously suggested that HLHS may result from variants in the neighboring FOXC2 and FOXL1 genes; however, screening for mutations in patients with HLHS revealed no pathogenic variants in those genes (Iascone et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism could explain our observation that in contrast to FOXF1 point mutations (Sen et al 2013b) and upstream deletion CNVs (Stankiewicz et al 2009; Szafranski et al 2013a; Szafranski et al 2014), genomic deletions of FOXF1 at its TAD boundary , and the flanking genes were associated with severe congenital heart defects, including hypoplastic left heart syndrome (HLHS) and SUA (Table 1 and Supplemental Table S1). Co-existence of HLHS and SUA has been well documented (Tasha et al 2014; Araujo et al 2015). We have previously suggested that HLHS may result from variants in the neighboring FOXC2 and FOXL1 genes; however, screening for mutations in patients with HLHS revealed no pathogenic variants in those genes (Iascone et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the number of terminal villi, as well as the vascular area and density were reported to be small at the end of pregnancies with hypoplastic left heart, which is one of the most clinically severe CHD in live births ( Jones et al, 2015 ). A study of fetuses with a single umbilical artery (SUA) showed that 13% of those fetuses had a cardiac anomaly, including hypoplastic left heart, coarctation of the aorta, tetralogy of Fallot, hypoplastic right heart, pulmonary atresia/stenosis, absent ductus venosus with cardiomegaly, left isomerism, right isomerism, and transposition of the great arteries ( Araujo Junior et al, 2015 ). These were also isolated heart defects as the study excluded cases with chromosomal abnormalities or extracardiac defects.…”
Section: Chd As a Secondary Defect To Placental Insufficiencymentioning
confidence: 99%
“…However, the association between isolated United States and congenital heart disease (CHD) is controversial. Some previous studies indicated that the incidence of CHD in SUA fetus increased to 5% regardless of chromosomal or extracardiac abnormalities, but several reports argued that in isolated SUA fetus with no additional risk factors for CHD did not increase the risk of CHD . Major cardiac defects were mostly detectable with four‐chamber view (4CV) and outflow tract view (OTV) during obstetric screening ultrasound .…”
Section: Introductionmentioning
confidence: 99%